Exploring the sintering process parameters on erosion-corrosion characteristics of Fe-Cr-Ni steels in artificial mine water. (October 2019) - Ige, O.O.; Oke, S.R.; Mphahlele, M.R.; Aribo, S.; Obadele, B.A.; Lephuthing, S.S.; Olawale, J.O.; Ajibola, O.O.; Daniyan, A.A.; Olubambi, P.A.
Abstract: This study investigates the erosion-corrosion behaviour of spark plasma sintered Fe-Cr-Ni relating additive and synergistic effects on the sintering temperature and time in mining and mineral processing industries. All tests were carried out using a rotating cylinder electrode system. The relative density has a relationship with the hardness values of the sintered alloys. The results linked the effects of the stainless steel sintering parameters (temperature and time) on the total mass loss, pure erosion, erosion-enhanced corrosion, and corrosion-enhanced erosion conditions. No correlation exists between the erosion-corrosion components and the densification mechanism since the porosity of the samples does not influence the sintered alloys behaviour. The surfaces indicated localized attack which increased with increasing time but decreased as the sintering temperature increased. Graphical abstract: Image 1 Highlights: Spark plasma sintered UNS 32205 was investigated in simulated mine water. Sintering process parameters influenced the erosion-corrosion behaviour of sintered steel. Sintering temperature and time of 1100 °C and 10 min is recommended for erosion-enhanced corrosion conditions. Sample sintered at 1000 °C and 10 min gives the optimal corrosion-enhanced erosion rate. Localized attacks decreased with increasing sintering temperature but increases with sintering time.